1968
DOI: 10.2466/pr0.1968.23.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Artifact in Studies of Cooperation

Abstract: Stimrnary.-A comparison of cooperative and noncooperative response rate data for some Ss indicated that reinforcement influenced both rates in the same proportion during acquisition and extinction periods, even though reinforcement was contingent upon the cooperative class of behavior only.An unambiguous demonstration of reinforcement control over cooperative behavior should show that changes in cooperative rate could not be interpreted as artifact, the result of reidorcement control over generalized respondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…High and steady response rates by both subjects would have produced a moderate number of reinforcers without regard to the behavior of the partner. Several studies (Brotsky & Thomas, 1967;Schmitt & Marwell, 1968;Vogler, 1968) suggest this was the case for some high-rate subjects.…”
Section: Discussionmentioning
confidence: 95%
“…High and steady response rates by both subjects would have produced a moderate number of reinforcers without regard to the behavior of the partner. Several studies (Brotsky & Thomas, 1967;Schmitt & Marwell, 1968;Vogler, 1968) suggest this was the case for some high-rate subjects.…”
Section: Discussionmentioning
confidence: 95%
“…For example, a steady response rate of 120 responses per minute by each subject would result in many reinforced or cooperative-like responses. If the responding were under the control of an individual high-rate contingency, individual responses that did not meet the 0.5-sec criterion for coordinated responding would be expected to increase and to be maintained along with responses meeting the 0.5-sec criterion (Brotsky and Thomas, 1967;Vogler, 1968;Schmitt and Marwell, 1968 It is more difficult to demonstrate that the cooperative behavior of a subject is under the control of the cooperative behavior of his partner in dependent cooperation procedures. It is simply unrealistic to expect that subjects will always respond in strict alternation such that the cooperative response of one subject is always the stimulus for the next cooperative response of his partner.…”
Section: Procedural Dimensionsmentioning
confidence: 99%
“…Although several other studies reported a functional relationship between temporally coordinated responding and reinforcement (Azrin & Lindsley, ; Cohen, ; Lindsley, ; Łopuch & Popik, ; Toledo & Benvenuti, ; Weingold & Webster, ), until recently no study has shown that coordinated responding occurs because of mutual reinforcement rather than as a byproduct of changes in individual response patterns (cf. Hake & Vukelich, ; Schmitt & Marwell, 1968; Tan & Hackenberg, ; Toledo et al, ; Velasco, Bevenuti, Sampaio, & Tomanari, 2017; Vogler, ).…”
mentioning
confidence: 99%